Adult GORD: advances and challenges in management. Issue 3 (March 2016) - Basu, Kumar
Abstract : Gastro‐oesophageal reflux disease (GORD) is a common and often chronic condition that is associated with poor quality of life and significant complications. This review provides a summary of the pathophysiology, assessment and current management of GORD in adults.